Disparities in antimicrobial consumption and resistance within a country: The case of beta-lactams in Argentina - Boni, Silvia (2021)
Objective. To describe bacterial resistance and antimicrobial consumption ratio at the subnational level in Argentina during 2018, considering beta-lactams group as a case-study. Methods. Antimicrobial consumption was expressed as defined daily doses (DDD)/1000 inhabitants. Resistance of Escherichia coli, Streptococcus pneumoniae, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus to beta-lactams was recorded. Resistance/consumption ratio was estimated calculating “R” for each region of Argentina, and this data was compared with other countries. Results. The most widely consumed beta-lactams in Argentina were amoxicillin (3.64) for the penicillin sub-group, cephalexin (0.786) for first generation cephalosporins, cefuroxime (0.022) for second generation; cefixime (0.043) for third generation and cefepime (0.0001) for the fourth generation group. Comparison between beta-lactams consumption and bacterial resistance demonstrated great disparities between the six regions of the country. Conclusions. The case-study of Argentina shows that antimicrobial consumption and resistance of the most common pathogens differed among regions, reflecting different realities within the same country. Because this situation might also be occurring in other countries, this data should be taken into account to target local efforts towards better antimicrobial use, to improve antimicrobial stewardship programs and to propose more suitable sales strategies in order to prevent and control antimicrobial resistance.